2015
DOI: 10.1016/j.proeps.2015.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Thermal Radiation Hazard from LPG Fireball

Abstract: The failure of the pressure vessel containing pressure liquefied petroleum gas leads to Boiling Liquid Expanding Vapour Explosion (BLEVE). Further, ignition of released gas results in the formation of fireballs. In the present paper the semi-empirical equations are presented that represent the impact assessment of thermal radiation hazards from the liquefied petroleum gas fireball. Also an attempt has been made to determine the safe separation distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…View factors from an infinitesimal surface to a spherical or a circular surface have practical applications in different engineering fields. Various studies can be found regarding the radiative heat exchange between an Earth orbiting satellite and the Earth [3,[10][11][12][13][14][15][16][17][18][19][20], the evaluation of thermal radiation from a fireball caused by hazardous material [21][22][23][24][25], and the evaluation of lighting conditions in the field of architecture [26].…”
Section: Introductionmentioning
confidence: 99%
“…View factors from an infinitesimal surface to a spherical or a circular surface have practical applications in different engineering fields. Various studies can be found regarding the radiative heat exchange between an Earth orbiting satellite and the Earth [3,[10][11][12][13][14][15][16][17][18][19][20], the evaluation of thermal radiation from a fireball caused by hazardous material [21][22][23][24][25], and the evaluation of lighting conditions in the field of architecture [26].…”
Section: Introductionmentioning
confidence: 99%
“…Vapour cloud explosions produce pressure waves. The effect of vapour cloud explosion depends on the peak incident overpressure due to pressure waves and the duration of the maximum overpressure [10].…”
Section: Modelling Of the Toxic Vapour Cloud Of Vinyl Acetatementioning
confidence: 99%
“…The first problem is usually sidestepped by stating that the thermal radiation from a BLEVE fireball is maximal and constant over the last two thirds of fireball duration (e.g. Casal 2008;Dhurandher et al 2015). In the first third, the radiation is not constant and increases from zero to a maximum value.…”
Section: Vulnerability Of Roadside Object To Thermal Damagementioning
confidence: 99%